1997
DOI: 10.1074/jbc.272.40.25243
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Armadillo Induced by Wingless, Dishevelled, and Dominant-negative Zeste-white 3 Leads to Elevated DE-cadherin inDrosophila Clone 8 Wing Disc Cells

Abstract: Drosophila genetic studies suggest that in the Wingless (Wg) signaling pathway, the segment polarity gene products, Dishevelled (Dsh), Zeste-white 3 (ZW-3), and Armadillo (Arm), work sequentially; wg and dsh negatively regulate zw-3, which in turn down-regulates arm. To biochemically analyze interactions between the Wg pathway and Drosophila E-cadherin (DE-cadherin) which bind to Arm, we overexpressed Dsh, ZW-3, and Arm, in the Drosophila wing disc cell line, clone 8, which responds to Wg signal. Dsh overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 82 publications
7
56
0
Order By: Relevance
“…We found that the endogenous DE-cadherin gene was transcriptionally activated in cl8Dshmyc cells only after prolonged overexpression of Dsh. Similar observations had been reported earlier (Yanagawa et al, 1997). Interestingly, in mouse hair follicles, Wnt signaling changes E-cadherin gene expression in the opposite manner, as it lowers E-cadherin transcription (Jamora et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…We found that the endogenous DE-cadherin gene was transcriptionally activated in cl8Dshmyc cells only after prolonged overexpression of Dsh. Similar observations had been reported earlier (Yanagawa et al, 1997). Interestingly, in mouse hair follicles, Wnt signaling changes E-cadherin gene expression in the opposite manner, as it lowers E-cadherin transcription (Jamora et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Immunoblot Analysis and Antibodies-Clone 8, S2Rϩ, and S2 cells grown to 80% confluence were lysed in lysis buffer and used to prepare samples for SDS-polyacrylamide gel electrophoresis, as described (22). The samples were loaded on 7.2% SDS-polyacrylamide gels, and the gels were then Western-blotted (21).…”
Section: Methodsmentioning
confidence: 99%
“…The samples were loaded on 7.2% SDS-polyacrylamide gels, and the gels were then Western-blotted (21). The antibodies used for Western analysis included the mouse monoclonal anti-Arm antibody N2-7A1 (29), the rat polyclonal anti-Dsh region I antibody (21), affinity purified rabbit anti-Wg IgG (30), the rat monoclonal anti-DE-cadherin antibody DCAD-2 (31), the rat monoclonal anti-Drosophila-␣-catenin antibody DCAT-1 (32), and peroxidase-conjugated secondary antibodies against mouse IgG (Bio-Rad), rat IgG (Jackson ImmunoResearch, West Grove, PA) and rabbit IgG (Cappel, Durham, NC), and the antibodies were diluted as described (22). Blots were visualized with enhanced chemiluminescence reagent (ECL, Amersham, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dvl proteins contain a DIX domain at the N terminus and two additional highly conserved domains: a central PDZ domain, and a DEP domain (8,9). Overexpression of Dvl in cells induces the accumulation of ␤-catenin and the activation of TCF (10,11). In response to Wnt signals, Dvl forms a heterodimer with Axin through their DIX domains, leading to enhanced association of glycogen synthase kinase-3␤ with Frat and decreased phosphorylation of ␤-catenin (6,12,13).…”
mentioning
confidence: 99%